ANALISIS TEMPERATUR SAMBUNGAN KABEL XLPE TEGANGAN MENENGAH 20 KV UNTUK BERBAGAI TORSI - Daru Tri Nugroho (Techno (Jurnal Fakultas Teknik, Universitas Muhammadiyah Purwokerto), 2011)
For insulated cable, heat factor is something that has to concern. Current capacity of a cable was influenced by characteristics of cable component. Losses at the cable will cause heat that would overcome through cable component with high resistance before it takes by environmental enclosed. The heating process will cause insulation material. Over heating process will fail insulation material and decrease lifetime of cable. Experiment on connector temperature of 20 kV middle voltage XLPE cable was doing by injecting constant alternating current from current injector to N2XEBY underground cable type that had cable connector. The test was by giving the different current level, using connector with different material, also with different torque for tightened connector bolt. In this test, we measure temperature on the cable junction every 5 minutes until the temperature equilibrium reaches. From the experiment we find that electrical current injection causes temperature to increase on cable parts until equilibrium. From relationship between current increasing and temperature increasing on cable parts we can see that maximum temperature increasing happened when it reaches equilibrium and time constant. We also see connector material and relationship torque for tightened cable connector bolt influence temperature and contact area increase. Key word : Termal characteristic, Cable connector, XLPE cable, Tourque, Equilibrium temperature